Interactions of p53 with poly(ADP-ribose) and DNA induce distinct changes in protein structure as revealed by ATR-FTIR spectroscopy. Issue 9 (20th March 2019) - Krüger, Annika; Stier, Anna; Fischbach, Arthur; Bürkle, Alexander; Hauser, Karin; Mangerich, Aswin
Abstract: Due to multiple domains and in part intrinsically disordered regions, structural analyses of p53 remain a challenging task, particularly in complex with DNA and other macromolecules. Here, we applied a novel attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopic approach to investigate changes in secondary structure of full-length p53 induced by non-covalent interactions with DNA and poly(ADP-ribose) (PAR). To validate our approach, we confirmed a positive regulatory function of p53's C-terminal domain (CTD) with regard to sequence-specific DNA binding and verified that the CTD mediates p53–PAR interaction. Further, we demonstrate that DNA and PAR interactions result in distinct structural changes of p53, indicating specific binding mechanisms via different domains. A time-dependent analysis of the interplay of DNA and PAR binding to p53 revealed that PAR represents p53's preferred binding partner, which efficiently controls p53–DNA interaction. Moreover, we provide infrared spectroscopic data on PAR pointing to the absence of regular secondary structural elements. Finally, temperature-induced melting experiments via CD spectroscopy show that DNA binding stabilizes the structure of p53, while PAR binding can shift the irreversible formation of insoluble p53 aggregates to higher temperatures. In conclusion, this study provides detailed insights into the dynamic interplay of p53 binding to DNA and PAR at a formerly inaccessible molecular level.